Answer:
n² - 2n + 2
Step-by-step explanation:
The difference in the pattern are odd numbers.
2 - 1 = 1
5 - 2 = 3
10 - 5 = 5
17 - 10 = 7
So there is a -2n in the nth term.
If we subtract 1 on each term.
0, 1, 4, 9, 16
We get whole squares.
So there is a n² in the nth term.
(1)² - 2(1)+ c = 1
1 - 2 + c = 1
-1 + c = 1
c = 2
The nth term is:
n²-2n+2
answer:
1. second choice
2. i'm not sure about this one, but i know it's not the second choice :)
3. first choice
4. second choice
i attached a image example if you need more help on it. hope this helps! ❤ from peachimin.
Answer:
The second one (answer of 3), but the other ones could've worked, they were just calculated wrong.
Step-by-step explanation:
Here's why each one did or didn't work:
First answer- you had the right idea by cancelling out the two in the denominator, however if you're going to divide 2, you have to divide it from everything in the equation. Meaning you would divide 4 by 2 to get 2, and then add the 1 + 2 to get final answer 3.
Second answer- since you added the numerator separately and then did the basic division, this worked.
Third one- similarly to the first one, you would have to also divide the 2 by 2 to get 1, then adding 1 + 2 to get 3.
Answer:If we got 560 pounds for 800 dollars and x pounds for 1 dollar, this means that x = 560*1/800 <=> x = 56/80. Performing the calulation we get that x = 0.7 . So the right answer is the final one.
Step-by-step explanation: